(untitled) (Journal of Engineering, 2007)
Aiming at energy preservation and depending on the production of years of expertise and hard work of international research laboratories in the area of energy preservation and finding alternatives and undepleted energy sources in all aspects and various areas of the world, all these institutions asserted on following the Sustainable Design Method. It pursues the integrated building design method, which is one of the modern methods in the domain of energy preservation . This method focuses on the building’s perfection from the very first stages of the design process, Through integration between the building components and mechanical services and supplementary systems in it and the impact exchange positively among them instead of being equipment used in a building that depends on the whole Building Approach , which has two key features , being circular and containing feedback concept , this makes it a frequent performing within the identification of the general conceptual framework. Considering oil and other new sources as unreliable as continues energy sources and synchronically and interactionally with the products of knowledge developments and technical products aiming at diminishing energy consumption and producing the light and thermal environment comfortable for staff at the human environment generally and industrially environment specifically , the study directed its research problem toward clarifying and demonstrating substance and effectiveness the method of the integration industrial building on the internal human and mechanical environment, aiming at demonstrating its importance as a consistent work mechanism that participate in organizing and correcting courses of the internal productive environment , plus demonstrating effect of its performance in clarifying the sustainable design interacted with the external environment to preserve energy . The aim is identifying the basic steps that role components of the integrated industrial building method to be a specific interactional method and a step context that explores work mechanism and the internal environment response to the external one to turn it to a visually , biologically and productively comfortable work environment. The research development on various studies and researches of many centers of the world , to be a base of the applied discussion of this study.